The Difference Between Using Proxy Server and VPN - David Dwiputra Kurniadi (Soegijapranata Catholic University, 2015)
In this era of globalization, it is important to get the lastest information or update. In this time people must know what internet is as almost every person ing computer or gadget, using internet to search for some information or something new.For example, looking for software, game through internet. But sometimes, there are some websites that cannot be opened as they have Internet Positive notificatio. To solve that problem, hacker found the solution by creating Proxy Server or VPN. In this time internet is very modern and very easy to access and there are a lot of Proxy Server and VPN that can be easly used.